Some new algorithms for reconfiguring VLSI/WSI arrays - Varvarigou, T.; Roychowdhury, V.P.; Kailath, T. (1990 proceedings, 1990)
Deals with the issue of reconfiguring processor arrays in the presence of faulty processors and fixed hardware resources. The models discussed consist of a set of identical Processing Elements (PEs) embedded in a flexible interconnection structure that is configured in the form of a rectangular grid. Furthermore in order to incorporate fault tolerance a given array has a pre-determined distribution of spare PEs. The general issue in reconfiguration is to replace faulty non-spare PEs by healthy spare ones, subject to given hardware constraints. The authors present some new algorithms for reconfiguring N*(N+1) arrays (where the spare PEs are configured in the form of a spare row) into N*N arrays when N of the PEs are faulty. The algorithms developed are simple and perform better than other reconfiguration algorithms presented in the literature.< >